Young People in Transition
XII, 208 p.
Keywords: The essays in this collection represent a major contribution to our understanding of youth and transitions to key areas of adult citizenship, including employment, independent living arrangements and political participation. The education of children and young people in 'citizenship' usually emphasizes either rights or responsibilities, through the concept of 'active citizenship'. The central concern of the book is to address the tensions and contradictions between the teaching of active citizenship and the real life difficulties many young people face in the practical transition to being adult citizens in modern life.